Comparison of AHP and BWM Methods Based on Geographic Information System for Determining Potential Zone of Pasir Batu Mining - Sabilla Ajrina, Adiba; Sarno, Riyanarto; Hari Ginardi, R.V. (2018 International Seminar on Application for Technology of Information and Communication, 2018)
Infrastructure development is increasing in order to fulfill the principle of sustainable development. This has influenced the need for building materials, one of which is Pasir Batu. Kediri Regency is one of the districts that produces the largest Pasir Batu in East Java Province. This is due to the existence of several rivers which is the area of lava flow resedimentation from Mount Kelud. Currently there are already some mining activities in Kediri Regency conducted at several potential points of Pasir Batu. This observe aims to map the region of mining areas assessed as probably the usage of Geographic Information System (GIS) and Multi Criteria Decision Making (MCDM) using Analitycal Hierarchy Process (AHP) and Best Worst Method (BWM) methods. GIS is used for records integration in order that zoning dedication may be visual, less difficult and more powerful. Whilst MCDM is used to decide the significance and weighting criteria. The criteria used are distance from main road, distance from nearest settlement, population density, lithology condition and morphological situation. The final result shows that the weight rank of two methods are different. In the calculation by the AHP method, we get the percentage weight as it follows: C4 (55,32 % ), C1 (26,72 % ), C5 (6,61%), C3 (6,10%) and the last is C2 (5,24%). Otherwise, in the calculation by the BWM method, we get the percentage weight as it follows: C4 (43,10%), C1 (24,60%), C2 (15,40%), C3 (12,30%) and the last is C5 (4,60%). The choice of criteria and deliberate hierarchy, additionally expert judgment to determine the level of significance of every criterion on AHP and BWM methods is very influential at the decision.